Transcriptome Profiling of Watermelon Root in Response to Short-Term Osmotic Stress - Yang, Yongchao; Mo, Yanling; Yang, Xiaozheng; Zhang, Haifei; Wang, Yongqi; Li, Hao; Wei, Chunhua; Zhang, Xian (PloS one, 2016)
Osmotic stress adversely affects the growth, fruit quality and yield of watermelon (Citrullus lanatus (Thunb.) Matsum. & Nakai). Increasing the tolerance of watermelon to osmotic stress caused by factors such as high salt and water deficit is an effective way to improve crop survival in osmotic stress environments. Roots are important organs in water absorption and are involved in the initial response to osmosis stress; however, few studies have examined the underlying mechanism of tolerance to osmotic stress in watermelon roots. For better understanding of this mechanism, the inbred watermelon accession M08, which exhibits relatively high tolerance to water deficits, was treated with 20% polyethylene glycol (PEG) 6000. The root samples were harvested at 6 h after PEG treatment and untreated samples were used as controls. Transcriptome analyses were carried out by Illumina RNA sequencing. A total of 5246 differentially expressed genes were identified. Gene ontology enrichment and biochemical pathway analyses of these 5246 genes showed that short-term osmotic stress affected osmotic adjustment, signal transduction, hormone responses, cell division, cell cycle and ribosome, and M08 may repress root growth to adapt osmotic stress. The results of this study describe the watermelon root transcriptome under osmotic stress and propose new insight into watermelon root responses to osmotic stress at the transcriptome level. Accordingly, these results allow us to better understand the molecular mechanisms of watermelon in response to drought stress and will facilitate watermelon breeding projects to improve drought tolerance.